Menghayati Kembali Iman Kristen Lewat Anateisme - Suarbudaya Rahadian (Asosiasi Teolog Indonesia, 2015)
With this essay, I aim to provide an alternative way of embracing Christian faith in this postmodern era, by considering both Richard Kearney's concept of anatheism as well as Slavoj Zizek's radical materialism. With the death of the God of ontotheology—as accomplished by modern atheism—Kearney posits anatheism to desribe a further experience of faith that